Fighting corruption in public procurement: a comparative analysis of disqualification or debarment measures - Williams-Elegbe, Sope (Hart Publishing, 2012)
Introduction -- Corruption, anti-corruption measures and disqualification -- An overview of procurement regulation, anti-corruption and disqualification policy in the jurisdictions -- The offences and the requirement for a conviction for disqualification -- Procedural issues affecting disqualification -- Disqualifying entities and the scope of disqualification -- Investigations -- The disqualification of persons related to a corrupt supplier -- The effect of disqualification on existing contracts -- Derogating from disqualification -- Remedies for affected suppliers.